Uncertainty Modeling of Fouling Thickness and Morphology on Compressor Blade - Limin Gao; Panpan Tu; Guang Yang; Song Yang (Aerospace)
To describe the fouling characteristics of compressor blades, fouling is categorized into dense and loose layers to characterize thickness and rough structures. An uncertainty model for dense fouling layer thickness distribution is constructed using the numerical integration and the Karhunen–Loève (KL) expansion method, while the Fouling Longuet-Higgins (FLH) model is proposed to address the uncertainty of loose fouling layer roughness. The FLH model effectively simulates the morphology characteristics of actual blade fouling and elucidates how parameters influence fouling roughness, morphology, and randomness. Based on the uncertainty modeling method, models for dense fouling layer thickness and loose fouling layer morphology are constructed, followed by numerical calculations and aerodynamic performance uncertainty quantification. Results indicate a 75.8% probability of aerodynamic performance degradation due to a dense fouling layer and a 97.2% probability related to the morphology uncertainty of a loose fouling layer when the roughness is 50 μm. This underscores that a mere focus on roughness is inadequate for characterizing blade fouling, and a comprehensive evaluation must also incorporate the implications of rough structures on aerodynamic performance.